How Smart Is “Smart Security”? Exploring Data Subjectivity and Resistance. Final Report - Baur-Ahrens, Andreas; Krüger, Marco; Ammicht Quinn, Regina; Leese, Matthias; Matzner, Tobias

Politische Öffentlichkeit und Big Data - Matzner, Tobias; Heesen, Jessica (Privatheit, Öffentlichkeit und demokratische Willensbildung in Zeiten von Big Data)

Sicherheitsethik in der Anwendung: Ein Praxistest gesellschaftlicher Begleitforschung - Matzner, Tobias; Ammicht Quinn, Regina (Sichere Zeiten?)

Ethik ohne Garantien - Matzner, Tobias (Ethik in den Wissenschaften)

Nanometer Scale Electronic Device Integration Using Side-Wall Deposition and Etch-Back Technology - Hilleringmann, Ulrich; Assion, F.; Vidor, F. F.; Wirth, G. I. (Journal of Machine to Machine Communications)
Keywords: General Medicine

Application of side-wall deposition and etch-back technology for nanometer scale device integration - Hilleringmann, Ulrich; Vidor, F.F.; Assion, F. (Proceedings of the 2nd Pan African International Conference on Science, Computing and Telecommunications (PACT 2014))

Extended event-driven modeling of a ΣΔ-fractional-N PLL including non-ideal effects - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (2014 21st IEEE International Conference on Electronics, Circuits and Systems (ICECS))

Fast and accurate event-driven simulation of a mixed-signal system using the example of a PLL - Hangmann, C; Hedayat, C; Hilleringmann, Ulrich (Proc. Int. Conf. Exhib. Integr. Issues Miniatured Syst.)

Religion und Krieg im Medium der Musik: Deutsche Oratorien im Ersten Weltkrieg - Höink, Dominik (Louis Spohr Symposium Braunschweig 2014: „Musik und Politik“. Politische Einflüsse auf Musikerbiografien und kompositorisches Schaffen von 1784 bis heute)

Louis Spohrs Der Fall Babylons und die ,Belsazardramen‘ seit Georg Friedrich Händel - Höink, Dominik (Die Oratorien Louis Spohrs. Kontext – Text – Musik)

Oratorium und Säkularisierung - Höink, Dominik (Kirchenmusikalisches Jahrbuch)

Die Oratorien Louis Spohrs. Kontext – Text – Musik

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

„There’s a better version of you out there.“ Überwachung, Personalisierung und die Sorge um sich im Selbstversuch - Shnayien, Mary (onlinejournal kultur & geschlecht)
In einem Selbstversuch testet die Autorin das Fitnessarmband UP der Firma Jawbone, das auf Basis gesammelter Daten personalisierte Ernährungs-, Schlaf- und Sportempfehlungen ausgeben kann, und zeichnet ihre Erfahrungen mit dem UP-System auf. Dabei wird Personalisierung sowohl als Technologie des Selbst als auch als Überwachungstechnologie bestimmt und die sich an dieser Intersektion ineinander verschränkenden Begehren, Wünsche und Ängste kartographiert.

Development of a Testing Method for the Identification of Friction Coefficients for Numerical Modeling of the Shear-Clinching Process - Müller, Martin; Vierzigmann, Ulrich; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Global competition as well as social and scientific megatrends strongly influence the modern car manufacturing industry. One of the most important approaches is the implementation of lightweight constructions. Therefore, the usage of high performance materials with tailored properties gains importance. For safety-relevant components such as automotive passenger cells it is necessary to minimize deformation to reduce the risk of injury for the vehicle occupants during a car accident. Thus, hot stamped high-strength steels have been established. High-strength and low formability of this kind of materials represent new challenges for joining technologies. One possibility to join high-strength steels is the newly developed shear-clinching technology. Due to the use of a combined cutting and joining process, the connection of dissimilar materials with high difference in strength and formability can be achieved. Further research to ensure process reliability and to improve the strength of the joint is required. One possible approach for this is the numerical investigation of the material flow during the joining process. Therefore, the definition of process parameters for the finite element model is necessary. A big impact on the quality of the results has the accuracy of the used friction values. As established testing methods are not suitable for modeling the rather complex tribological system between the joining partners of the shear-clinching process, an innovative testing method is needed. Studies in the field of sheet-bulk metal forming already demonstrated the applicability of the ring compression test for sheet metals. This paper presents a concept for the adaption of the ring compression test to the specific needs of the investigated shear-clinching process. The numerical identification of the friction coefficients is validated by experimental data and first results are qualified by experimental and simulative shear-clinching joints.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Deutungskonflikte um automatisierte Videoüberwachung: Zur sozialen Konstruktion einer Technologie als Instrument der Kriminalitätsbekämpfung - Hälterlein, Jens; Möllers, Norma (Grenzenlose Sicherheit?)

Intelligente Videoüberwachung: eine Handreichung, IZEW Materialien Band 11 - Hälterlein, Jens; Ammicht Quinn, Regina; Koch, Heiner; Held, Cornelius; Matzner, Tobias; Krumm, Julia; Flack, Jaqueline; Markel, Petra; Möllers, Norma; Wittmann, Philipp

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities